Frequency of Pregnancy Induced Hypertension in Teenage Pregnancy, Presenting in a Tertiary Care Hospital - Fatima Bibi, Bushra Sayyed, Mehreen Yousaf Rana, Erum Bano, Zahra Amjad, Faryal Zafar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of pregnancy induced hypertension in teenage pregnancy, presenting in a tertiary care hospital. Design of the Study: It’s a descriptive case series Study Settings: This study was done at Department of Gynaecology & Obstetrics, Ziauddin Hospital, Karachi from January 2021 to June 2021. Material and Methods: Total 163 women with gestational age 20 and more weeks, age 10 to 19 years, singleton pregnancy, and with any parity were included in the study. On the basis of clinical examination, pregnancy comprised hypertension was diagnosed. If any patient had BP equal or more than 140/90 on more than two separate occasions, then it was considered as hypertensive. Patients were followed at 24, 28, 34, 36, and 38 weeks till delivery to look for development of Pregnancy induced hypertension. If patient developed any complications, was admitted and managed accordingly. By using computer program SPSS-17, data was entered and analyzed. For post stratification Chi-square test was applied and p-value ≤0.05 was considered as significant. Results of the Study: The average maternal age was 16.53±1.94 years. The mean parity was 3.03±1.44 and mean gravidity was 2.80±1.44. The mean gestational age was 31.17±3.52 weeks, with range 16(21–37) weeks. Age of 49 women was ≤15 years and age of rest of the 114 women patients was >15 years. The parity of gravidity of 113 women was ≤3 and it was >3 in 50 women. The parity of 131 women was ≤3 and in the 32 women it was >3. The gestational age of 73 women was ≤30 weeks and gestational age of 90 women was >30 weeks. The pregnancy induced hypertension was found in 24(14.7%) females who are expecting involved in the research. Among women with PIH the mean age was 16.46±2.14 years and mean gestational age was 30.83±3.26 weeks. The results showed no statistically significant association of maternal age, gravidity, parity, and gestational age with pregnancy induced hypertension. Conclusion: For higher incidence of pregnancy induced hypertension, the younger maternal age is a significant risk factor.